Fuzzy systems toolbox for use withMATLAB - Beale, Mark; Demuth, Howard (PWS productivity tools., 1994)
Designs, simulates, and tests fuzzy systems within the MATLAB environment. Supplements MATLAB by performing numerical calculations and graphic visualizations. Includes sample fuzzy systems applications.